Egyptian-Ethiopian Relations 1952-2015 - Salim Hanna, Etlal (Opción, 2019)
The nature of Egyptian-Ethiopian relations in the period 1952-2015 constituted an important regional and international presence, especially with the Western countries trying to get closer to Ethiopia to ensure their interests in the Middle East. Hence our study to show the nature of bilateral relations be- tween the two countries during the period 1952-2015, and to identify the causes of escalation and conflict and the ongoing conflict between them, based on the changes that occur in the political systems of the two countries and trends The issue of borders, water and the construction of dams on the Nile basin are among the most important issues that have been and still lead to tension and escalation between them, which has become one of the most important prob- lems facing them because they are mainly linked to the national security of the two countries, especially the issue of water, which has become a political and economic weapon, which began to worsen because of Population growth and economic development.